2020
DOI: 10.1039/c9nj04335g
|View full text |Cite
|
Sign up to set email alerts
|

The influence of support composition on the activity of Cu:Ce catalysts for selective catalytic reduction of NO by CO in the presence of excess oxygen

Abstract: Excellent catalytic performance for NO reduction by CO in the presence of 5% O2 over Cu1:Ce3/Al2O3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 65 publications
(78 reference statements)
0
4
0
Order By: Relevance
“…The Cu1:Ce3/CNT catalyst displayed the highest NO conversion of 96% at 220 • C, attributed to its high concentration of surface oxygen vacancies (SOVs), high Cu + species content, superior reducing capability, and the synergistic effect between SOV and Cu + species. Furthermore, Gholami et al [39] investigated the denitration performance of a string of Cu1:Ce3 catalysts supported on various supports (CNTs, AC, TiO 2 , γ-Al 2 O 3 , and SiC) in the presence of excess O 2 (5 vol.%), and found that Cu1:Ce3/Al 2 O 3 catalyst possessed the highest catalytic performance, with 71.8% NO conversion at 420 • C, mainly ascribed to the enrichment of catalytically active centers of Cu on the Al 2 O 3 support. Interestingly, it was observed that with the increase in O 2 concentration from 2% to 5%, the conversion of NO increased slightly.…”
Section: Bimetallic Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cu1:Ce3/CNT catalyst displayed the highest NO conversion of 96% at 220 • C, attributed to its high concentration of surface oxygen vacancies (SOVs), high Cu + species content, superior reducing capability, and the synergistic effect between SOV and Cu + species. Furthermore, Gholami et al [39] investigated the denitration performance of a string of Cu1:Ce3 catalysts supported on various supports (CNTs, AC, TiO 2 , γ-Al 2 O 3 , and SiC) in the presence of excess O 2 (5 vol.%), and found that Cu1:Ce3/Al 2 O 3 catalyst possessed the highest catalytic performance, with 71.8% NO conversion at 420 • C, mainly ascribed to the enrichment of catalytically active centers of Cu on the Al 2 O 3 support. Interestingly, it was observed that with the increase in O 2 concentration from 2% to 5%, the conversion of NO increased slightly.…”
Section: Bimetallic Catalystsmentioning
confidence: 99%
“…Therefore, O 2 existing in the CO-SCR reaction system has an inhibitory effect on NO reduction. Gholami et al [39] investigated the effect of O 2 (2% or 5%) on the denitration performance of the Cu1:Ce3/Al 2 O 3 catalyst for the CO-SCR reaction system, and found that compared with the case without O 2 , the conversion of NO decreased from 59.3% to nearly 40% after 2% O 2 was introduced at 300 • C, but increased to 43.3% when 5% O 2 was introduced. They believe that this is because more O 2 is adsorbed on the surface of the catalyst and then cleaved to O (ad) , thereby promoting the formation of NO 2 , which can further rapidly react with CO to form N 2 and CO 2 .…”
Section: Effect Of Omentioning
confidence: 99%
“…However, it has been restricted due to its high cost and rare reserves. Several non-noble metal oxides were reported for the NO reduction owing to their low price, such as Cu−Ce/TiO 2 [8], Co 3 O 4 [9], Cu/CeO 2 −Fe 2 O 3 [10], Fe/ZSM-5 [11], FeO x /CeO 2 [12], and so on. Still, most of them have low reaction activity and N 2 selectivity at low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have recently been devoted to reduce and control NO x from the air using different technologies, such as selective catalytic reduction (SCR) that converts harmful NO x to harmless N 2 . Considerable attention has been given to the development of SCR of NO x using CO, which can efficiently remove NO and CO co-existing in many industrial exhaust gases [1][2][3]. However, this method has several challenges, such as resistance to O 2 and SO 2 , ensuring low-temperature activation, and durable operation.…”
Section: Introductionmentioning
confidence: 99%